The Security Challenges of the Rhythmprint Authentication - Nakinthorn Wongnarukane; Pramote Kuacharoen (Institute of Advanced Engineering and Science, 2018)
The Rhythmprint authentication combines an advantage of the traditional keystroke authentication and the multi-touch technology based on a touchable device such as touchpad on a laptop, a smartphone and a tablet. With the Rhythmprint authentication, the user is less likely to suffer from shoulder surfing and eavesdropping attacks. This research provides empirical evidence to verify the security performance of the Rhythmprint authentication comparing to the traditional keystroke authentication for shoulder surfing and eavesdropping attacks, when the user tries to login to a website on a laptop for 10 times in a public place while the attacker stands behind. The experimental results show that the Rhythmprint authentication provides higher security than the traditional keystroke authentication in both shoulder surfing and eavesdropping attacks.